Literature Review: The Effectiveness of Tabletop Disaster Exercise on Disaster Preparedness - Nur Adi Darmawan; Ridlwan Kamaluddin (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Backgrounds: Disasters often come without warning and canresulted in a lot of losses. Preparedness is a form of activity carried out to anticipate disasters. One of the activities that can be done to improve preparedness is by simulating using the Tabletop Disaster Exercise (TDE) media. Therefore, it is important to identify the effectiveness of tabletop disaster exercise on disaster preparedness.Objective : To assess the effectiveness of tabletop disaster exercise on disaster preparedness.Methods: The study was conducted based on the study. The search is limited to articles published in 2017-2021, full text, using the tabletop disaster exercise method with the type of original research. The databases used are Pubmed, National Library of Indonesia, and Google Scholar with the keywords tabletop disaster exercise, disaster, preparedness.Results: Five articles were found on the implementation of TDE which aims to improve preparedness and knowledge of disasters. The article contains knowledge, self-confidence, understanding of the role of disaster preparedness. The results of the analysis carried out on the five articles taken were the effectiveness of the tabltop disaster exercise on disaster preparedness with a value of p = 0.001 or p 0.05.Conclusion: The Tabletop Disaster Exercise is effectively implemented to improve disaster preparedness.Keywords: tabletop disaster exercise, disaster, preparedness